Shale as a Source of Organic Carbon in FloodplainSediments of a Mountainous Watershed. Issue 2 (20th February 2020) - Fox, Patricia M.; Bill, Markus; Heckman, Katherine; Conrad, Mark; Anderson, Carolyn; Keiluweit, Marco; Nico, Peter S.
Abstract: Shales contain high levels of organic carbon (OC) and represent a large fraction of the Earth's reduced carbon stocks. While recent evidence suggests that shale‐derived OC may be actively cycled in riverine systems, this process is poorly understood and not currently considered in global C models. Through the use of sediment density fractionations, extractions, radiocarbon measurements, and chemical characterization, we provide information on the abundance, chemistry, and mobility of shale‐derived OC in floodplain sediments of a shale‐rich mountainous watershed. The heavy fraction of the sediment, representing mineral‐associated OC, is the largest (84 ± 6% of TOC) and oldest (Δ 14 C values −224 to −853‰) OC pool. Evidence of shale‐derived OC is observed in all sediment C pools (i.e., occluded light fraction, water‐soluble, and pyrophosphate‐extractable) except the free light fraction, which is entirely modern. Relatively consistent chemistry was observed across samples for extracted and density‐separated OC, despite wide ranges of Δ 14 C values. Carbon spectroscopy revealed that floodplain sediments had a higher degree of functionalized aromatic groups and lower carbonate content compared to shale collected nearby, consistent with chemical alteration and mixing with other C sources in the floodplain. We estimate that approximately 23–34% of sediment OC is derived from shale, with implications for other shale‐derived elements (e.g., N). This study demonstrates the important contribution of shale‐OC, particularly in environments with low litter inputs. The large impact of radiocarbon‐dead shale‐OC, which has a thermally altered chemical structure distinct from plant litter, on Δ 14 C values and reactivity of sediment‐OC must be considered. Plain Language Summary: Shales contain high levels of organic carbon (OC) and represent a large fraction of the Earth's total carbon stocks. While recent evidence suggests that shale‐derived OC, which is millions of years old, may be actively cycled in riverine systems, this process is poorly understood and not currently considered in global C models. In this study, we analyze sediments collected from the floodplain of the East River, CO, located in a high‐elevation mountainous watershed underlain by shale bedrock, to determine the importance and mobility of shale‐derived OC in this environment. OC closely associated with sediment minerals is the largest (84 ± 6%) and oldest OC pool, containing a large, but variable, amount of shale‐derived OC. Evidence of shale‐derived OC is also observed in other sediment OC pools which are considered to be more mobile and more easily degraded to carbon dioxide by bacteria (e.g., water‐soluble). This study concludes that there are two primary OC sources in floodplain sediments, plant‐litter and shale‐derived OC, each with distinct chemical characteristics and reactivity. We estimate that 23–34% of the sediment OC is derived from shale, demonstrating the important contribution of shale‐OC to the carbon cycle at this site, particularly in environments with low plant‐litter inputs. Key Points: Shale‐derived organic carbon (OC) accounts for an estimated 23–34% of total OC in floodplain sediments of a shale‐dominated landscape The mineral fraction contains the largest and oldest pool of OC, and shale‐derived OC is also observed in pools considered to be actively cycled Implications for shale as an unrecognized source of global C and other rock‐derived elements and for interpretation of bulk 14 C data